Investigating negotiation of meaning in EFL children with very low levels of proficiency - Lázaro, Amparo; Azpilicueta, Raúl (International Journal of English Studies, 2015)
Numerous studies hold that interaction has beneficial effects on second language acquisition among adults and children in second language contexts. However, data from children learning English as a foreign language are still unavailable. In order to fill this research niche, this study examines the conversational interactions of 8 pairs of young (ages 7-8) learners of English as a foreign language while playing a game in the classroom. The objective is to document which conversational strategies these learners use and to compare them to those previously reported for other populations. The analysis of our data shows that these children negotiate significantly less than other populations but use a variety of strategies to negotiate for meaning. Also, they resort to the L1 on some occasions and use explicit correction quite often. In light of these results we will argue in favour of using these types of interactive activities in the classroom.